British Columbia Native Indians: Distribution of Ethnic Groups - 1850 (monochrome) (Government of British Columbia, 1956)
Map of distribution of indigenpus ethnic groups ca. 1850. Map was produced by the Government of British Columbia in 1956. Divisions are based on linguistic groups and include demarcation by language family; language group and dialect groups. GOV-4 is a colour version of this map.